Common genetic variation in KATNAL1 non-coding regions is involved in the susceptibility to severe phenotypes of male infertility - IVIRMA Group (2022)
© 2022 The Authors. Andrology published by Wiley Periodicals LLC on behalf of American Society of Andrology and European Academy of Andrology.